Islam, Averrorism and Democracy: A Review of Public Education and Social Equity - Alkahtani, Hezam Sultan J.; Muslimin, JM; Muttaqin, Fakih Fadilah; Hidayat, Syahrul Ramadhan; Ugli, Abdulbosit Rakhimjonov Rafikjon (LETIGES, 2025)
This study explores the relationship between Islam, Averroism, and democracy within public education, emphasizing their impact on social equity. It investigates how Islamic principles such as justice (ʿadl), consultation (shūrā), and public interest (maṣlaḥah), alongside Ibn Rushd’s rationalist philosophy, can support the development of inclusive and democratic educational frameworks. Employing a qualitative approach, the research integrates philosophical and theological analysis with a review of educational policies in Muslim-majority countries, analyzing primary and secondary sources to assess the alignment of religious ethics, rational inquiry, and democratic values in education. Using thematic analysis, the study identifies challenges in balancing traditional religious curricula with modern pedagogical methods, particularly in fostering critical thinking and democratic participation. Despite these obstacles, it underscores the potential for integrating religious ethics and rationalist thought to establish more equitable and participatory education policies. By synthesizing Islamic traditions, Averroist rationalism, and democratic ideals, this research provides a novel perspective on education reform and offers valuable insights for policymakers, educators, and researchers. Future studies should explore the empirical application of this framework across diverse educational settings to enhance inclusivity and social justice.